2021
DOI: 10.1177/2397847320988496
|View full text |Cite
|
Sign up to set email alerts
|

Acute electronic vapour product whole aerosol exposure of 3D human bronchial tissue results in minimal cellular and transcriptomic responses when compared to cigarette smoke

Abstract: The use of electronic vapour products (EVPs) continues to increase worldwide and with advances in cell culture systems, molecular biology and the computational sciences there is also accumulating evidence of their potential reduced toxicity and reduced potential harm when compared to cigarette smoke. To further understand the potential risks and health effects associated with exposure to EVP aerosols we have assessed the cellular and transcriptomic response from a commercially available lung tissue culture sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Although we have not looked at transcriptomics in this study, in a related study by Phillips et al (2021) assessed the acute response to non-cytotoxic doses of my blu and 3R4F. No pathological changes were observed at either recovery time point from any exposure (48 h).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although we have not looked at transcriptomics in this study, in a related study by Phillips et al (2021) assessed the acute response to non-cytotoxic doses of my blu and 3R4F. No pathological changes were observed at either recovery time point from any exposure (48 h).…”
Section: Discussionmentioning
confidence: 95%
“…Air and EVP aerosol exposure had no effect on CBF, CAA nor TEER at 48 h. Exposure to cigarette smoke resulted in a decrease in TEER and an increase in CBF and the release of proinflammatory cytokines at both recovery time points. Although the number of significantly expressed genes was minimal following exposure to EVP aerosol, exposure to 3R4F smoke resulted in a significant upregulation of several disease relevant pathways (oxidative stress and inflammation) ( Phillips et al, 2021 ). These functional findings as expected are mirrored in the current longer-term study we report here (28 days) with EVP and 3R4F.…”
Section: Discussionmentioning
confidence: 99%
“…The different ratio of cilia-bearing to mucus-producing cells between the tissues may be the reason for this difference. The average CBF of MucilAir™ tissues in the literature are indicated as 15.8 Âą 0.3 Hz and 11.7 Âą 1.2 Hz [ 43 , 45 ], and Beyeler et al observed higher CBF in the peripheral than in the central region [ 18 ]. This trend was also to some extent seen in the EpiAirway™ tissues but not in the MucilAir™ tissues of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic profiling is a powerful tool for identifying cellular reprogramming consequential to environmental stress. Transcriptional profiling of vape fluid exposure has primarily involved cell culture models examining acute changes after short-term exposure protocols ( 80 , 81 , 82 , 83 , 84 ). Such studies have implicated vape juice for induction of genes associated with inflammation, metabolic/biosynthetic processes, extracellular membrane, apoptosis, lipid metabolism, and hypoxia.…”
Section: Discussionmentioning
confidence: 99%